PERAN SOSIALISASI PAJAK DALAM MEMPERKUAT KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR: STUDI MODERASI - Aristyani, Luh Riska; Yasa, I Nyoman Putra; Astawa, I Gede Putu Banu (UNHI Press, 2025)
Motor Vehicle Tax (PKB) is a regional tax that serves as the largest contributor to the Regional Original Revenue (PAD) structure. However, data presents the existence of PKB payment arrears of 55.17% in 2023, reflecting the low compliance of taxpayers. This non-compliance has the potential to reduce regional revenue and negatively impact PAD. Grounded in attribution theory, this study examines the role of tax socialization in strengthening the influence of tax understanding and the implementation of tax incentives on motor vehicle taxpayer compliance. The study focuses on motor vehicle taxpayers in Buleleng Regency as an accessible population. The minimum sample size was calculated by using G*Power software. Data were collected through questionnaires and analyzed using the Moderated Regression Analysis (MRA) test. The findings reveal that tax understanding and the implementation of tax incentives positively and significantly affect motor vehicle taxpayer compliance. However, tax socialization does not significantly strengthen the impact of tax understanding and the implementation of tax incentives on taxpayer compliance.